Performance Of Trichogramma Evanescens Westwood Egg Parasitoid Against Angoumois Grain Moth, Sitotroga Cereallela. (Olivier) - Akter, T Al (Journal of the Asiatic Society of Bangladesh, Science, 2015)
The performance of Trichogrammaevanescens Westwood egg parasitoid againstAngoumois grain moth, Sitotrogacereallela. (Olivier) was investigated during theperiod from January 2011 to May 2011. The results showed that the highest per cent ofadult parasitoid emergence (98.94%) from parasitized eggs of S. cerealella was by T.evanescens. The duration of adult parasitoid emergence varied from 7-8 days. Thelongevity of T. evanescens adult that emerged from parasitized eggs varied from 3-4days. In consideration of rate of parasitization by using different number of parasitoids,the highest (98.00%) parasite eggs were recorded from 50 pairs of parasitoids whichwas statistically identical (94.25%) with 35 pairs and followed (93.25%, 92.75% and92.25%) by 25, 20 and 15, pairs respectively. The rate of parasitism increased withincreased number of parasitoids. A positive correlation exists between per centparasitism and adult parasitoid emergence from parasitized eggs. It reveals that the T.evanescens has potential in the biological control of Angoumois grain moth, of S.cerealella. Asiat. Soc. Bangladesh, Sci. 41(1): 95-103, June 2015